Nurses' experiences with health care in pain clinics: A qualitative study - Kine Gjesdal; Elin Dysvik; Bodil Furnes (Elsevier, 2019)
Background: Recent research has focused on the effectiveness of different treatment regimens in pain clinics, where a call for more multifaceted treatment has been highlighted. Less attention has been paid to improvements within pain clinics, and how registered nurses-who usually play a key role-perceive and experience the accessibility, treatment options and follow-up offers at public pain clinics. Objective: The overall aim was to explore and describe how nurses experience health care provided to patients with chronic non-cancer pain at pain clinics. Methods: We used 10 individual interviews with nurses working at 10 different public pain clinics in Norway. The interviews were analyzed using qualitative content analysis. Results: One theme was developed from the content analysis: "Nurses' striving to provide whole-person care in pain clinics." The nurses experienced allocation of limited resources as challenging, especially when the dilemma between accepting new patients from the waiting list and offering follow-up to existing patients became apparent. Multifaceted treatment was perceived as vital, although resources, priorities, and theoretical understanding of pain within the team were challenging. Conclusions: The needs for multifaceted and integrated treatments in chronic pain management were obvious, although this approach appeared to be too demanding of resources and time. Stronger cooperation between pain clinics in specialist care and health care providers in primary care to ensure better patient flow and treatment is required. Emphasis is placed on coherent theoretical approaches to pain management within the team in the pain clinics to ensure whole person care. Keywords: Holistic care, Pain, Pain clinics, Pain management, Nurses